Adat Court in the Context of Supply Chain Legal Pluralism Management in Indonesia - Hazar Kusmayanti; Efa Laela Fakhriah; Bambang Daru Nugroho; Djanuardi Djanuardi (International Journal of Supply Chain Management, 2020)
The Indonesian supply chain legal system in which there are three recognized laws, namely the customary supply chain legal system, the Islamic supply chain legal system and Western law, the three laws are mutually sustainable with each other to achieve the same goal, but in the course of the three laws follow the rules contained in the law. Scholars call this supply chain legal Plurarism. The issue of supply chain legal pluralism is the resolution of customary disputes through adat courts, which formally there is no supply chain legal juridical formal in Indonesia. Researchers will try to examine the position of Adat Court in the context of supply chain legal pluralism in Indonesia and know the practice of Adat  courts in Indonesia.Supply chain legal pluralism launches criticism of what John Griffiths called the ideology of supply chain legal centralism. Supply chain legal centralism interprets the law as "state law" which applies uniformly to all people who are in the country's jurisdiction. Thus, there is only one law and its judicial institution that is enforced in a country, namely state law and state justice. As is well known, the main problems of state justice are the achievement of the principle of fast, simple and light, convoluted dispute resolution, accumulation of cases and the significant cost of the parties makes the role of adat justice very necessary. The types of problem solving offered by the formal supply chain legal system also sometimes get different views and are considered inadequate and lack the sense of justice of the people who still hold their own supply chain legal traditions. In practice, customary courts in some regions still function well, especially for areas that are very thick with customary law and their communities are still subject to customary law. As in Minangkabau, the traditional court is known as the Density of Nagari Adat, in Aceh known as the traditional court of Sarak Opat, the local government also supports the existence of a customary court by establishing regional regulations which limit the disputes which must be tried in an adat court or court country.